The impact of Seven Major Noncommunicable Diseases on Direct Medical Costs, Absenteeism, and Presenteeism in Gulf Cooperation Council countries - Finkelstein, Eric Andrew; Malkin, Jesse D.; Baid, Drishti; Alqunaibet, Ada; Mahdi, Khaled; Hamad Al-Thani, Mohammed Bin; Bin Belaila, Buthaina Abdulla; Nawakhtha, Ebrahim Al; Alqahtani, Saleh; El-Saharty, Sameh; Herbst, Christopher H. (Taylor and Francis, 2022)
To estimate the current burden of seven major noncommunicable diseases on direct medical costs, absenteeism, and presenteeism in the six countries in the Gulf Cooperation Council: Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, and the United Arab Emirates. The economic burden of noncommunicable diseases in Gulf Cooperation Council countries is substantial, suggesting that successful preventive interventions have the potential to improve both population health and reduce costs. Further research is needed to capture a broader array of noncommunicable diseases and to develop more precise estimates.